Nongranulomatous Anterior Uveitis Associated With Alendronate Therapy - Salmen, Siham; Berrueta, Lisbeth; Sánchez, Nelly; Borges, Lérida (Investigación Clínica, 2009)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Caslon224 Bk BT"; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-alt:"Times New Roman"; mso-font-charset:0; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:0 0 0 0 0 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>We describe a case of acute nongranulomatous anterior uveitis associated with alendronate therapy, in an adult woman, without medical history of previous diseases, except for intercurrent problems of osteoporosis. The symptoms disappeared abruptly after anti-inflammatory therapy and discontinuation of alendronate. Side effects associated with ocular inflammation have been recently documented in 3 patients under alendronate therapy. Clinical and laboratory diagnosis of ocular inflammation syndromes are also reviewed